Linker Protein Repair of LAMA2 Dystrophic Neuromuscular Basement Membranes - Yurchenco, Peter D.; McKee, Karen K. (Frontiers in Molecular Neuroscience, 2019)
An understanding of basement membrane (BM) assembly at a molecular level provides a foundation with which to develop repair strategies for diseases with defects of BM structure. As currently understood, laminins become anchored to cell surfaces through receptor-mediated interactions and polymerize. This provisional matrix binds to proteoglycans, nidogens and type IV collagen to form a mature BM. Identification of BM binding domains and their binding targets has enabled investigators to engineer proteins that link BM components to modify and improve their functions. This approach is illustrated by the development of two linker proteins to repair the LAMA2-deficient muscular dystrophy (LAMA2-MD). Dystrophy-causing mutations of the LAMA2 gene product (Lm alpha2) disrupt the BM molecular architecture, destabilizing it. In a mild ambulatory type of the dystrophy, Alpha2LN mutations in laminin-211 prevents polymerization. In the more common and severe non-ambulatory type (MDC1A), an absent Lm2 subunit is re-placed by the naturally-occurring Lm alpha4 subunit that is normally largely confined to the micro-vasculature. The compensatory laminin, however, is a poor substitute because it neither polymerizes nor binds adequately to the anchoring receptor -dystroglycan. A chimeric laminin-binding protein called alphaLNNd enables laminins with defective or absent LN domains to polymerize while another engineered protein, miniagrin (mag), promotes efficient alpha-dystroglycan receptor-binding in otherwise weakly adhesive laminins. Alone, LNNd enables Lm211 with a self-assembly defect to polymerize and was used to ameliorate a mouse model of the ambulatory dystrophy. Together, these linker proteins alter Lm411 such that it both polymerizes and binds DG such that it properly assembles. This combination was used to ameliorate a mouse model of the non-ambulatory dystrophy in which Lm411 replaced Lm211 as seen in the human disease. Collectively, these studies pave the way for the development of somatic gene delivery of repair proteins for treatment of LAMA2-MD. The studies further suggest a more general approach of linker-protein mediated repair in which a variety of existing BM protein domains can be combined together to stabilize BMs in other diseases.